2011
DOI: 10.1007/s00128-011-0495-5
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Effects of Curcumin on Sodium Fluoride-Induced Intoxication in Rat Erythrocytes

Abstract: Curcumin is well known for its potent antioxidant activity. The result of numerous studies showed that antioxidants can protect against fluoride-induced toxicity. In the present study, protective effects of curcumin against sodium fluoride-induced toxicity in rat erythrocytes were evaluated. Curcumin (10 and 20 mg/kg) and vitamin C (10 mg/kg) were administrated intraperitoneally for 1 week followed by sodium fluoride (600 ppm) treatment for next week. Erythrocytes were isolated and superoxide dismutase and cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…Furthermore, we found that glutathione levels in erythrocytes diminished after NaF exposure, suggesting an induction of oxidative stress. These fi ndings, together with the results obtained for the positive control, vitamin C, were in agreement with our previous study (20) where in vivo amelioration of NaF-mediated oxidative stress was recorded in curcumin pre-treated rats. Our fi nding that gallic acid effectively protected rat erythrocytes suggests that the antioxidant effect of the compound at the tested dosage in vivo was more prevalent than its prooxidative effects.…”
Section: Figure 4 Effects Of Gallic Acid and Vitamin C On Gshsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, we found that glutathione levels in erythrocytes diminished after NaF exposure, suggesting an induction of oxidative stress. These fi ndings, together with the results obtained for the positive control, vitamin C, were in agreement with our previous study (20) where in vivo amelioration of NaF-mediated oxidative stress was recorded in curcumin pre-treated rats. Our fi nding that gallic acid effectively protected rat erythrocytes suggests that the antioxidant effect of the compound at the tested dosage in vivo was more prevalent than its prooxidative effects.…”
Section: Figure 4 Effects Of Gallic Acid and Vitamin C On Gshsupporting
confidence: 93%
“…In a previous study (20), we introduced a rat model of fl uoride-induced oxidative damage. In order to continue our work on P. peltatum and validate the therapeutic potential of gallic acid from natural sources, the present study was designed to study the in vivo protective effect of gallic acid against oxidative damages in rat erythrocytes.…”
mentioning
confidence: 99%
“…19 As an efficient reactive oxygen scavenger including NO and iron chelator, it appears that quercetin improves the oxidant-antioxidant imbalance created by fluoride intoxication. 21 As a multifunctional molecule, however, other mechanisms of action are also likely to be associated with quercetins nephroprotective effect.…”
Section: Discussionmentioning
confidence: 99%
“…Natural product such as phenolics and flavonoids can protect the body against free radical induced toxicity through different antioxidative mechanisms (Nabavi et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%